Rhythmanalysis in Doris Lessing’s “Storms”: London from a Critical View of Everyday Life - Özge Üstündağ Güvenç (Nalans, 2020)
The interaction between humans and space has recently been one of the dominant issues in the works of contemporary century to explain how thinking about space has evolved from a fixed and limiting framework to an alternative multidimensional understanding of it where human interventions create alternative space. This study aims not only to move beyond the setting descriptions in a literary text but also to open up Henri Lefebvre’s theory of space, particularly his notion of rhythmanalysis, that have been utilized in the fields of architecture, sociology, geography, urban and regional planning to include literature as well. To this end, Doris Lessing’s sketch, “Storms” from the collection London Observed: Stories and Sketches, will be analysed since it displays various life trajectories in London and provides a critical view of the city from two different perspectives –  that of the taxi driver and of the narrator – which contradict each other. Focusing on their interpretations of London and to what extent they are able to sense and make meaning of rhythms, thus, offers a new mode of observing the movement and continuity of life, complementing the apprehension of the relationship between humans and the spaces they occupy, and what feelings they attribute to.